2017
DOI: 10.3847/2041-8213/aa7412
|View full text |Cite
|
Sign up to set email alerts
|

On the Maximum Mass of Accreting Primordial Supermassive Stars

Abstract: Supermassive primordial stars are suspected to be the progenitors of the most massive quasars at z ∼ 6. Previous studies of such stars were either unable to resolve hydrodynamical timescales or considered stars in isolation, not in the extreme accretion flows in which they actually form. Therefore, they could not self-consistently predict their final masses at collapse, or those of the resulting supermassive black hole seeds, but rather invoked comparison to simple polytropic models. Here, we systematically ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
169
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(179 citation statements)
references
References 44 publications
10
169
0
Order By: Relevance
“…The large accretion rates of 0.1 M yr −1 or more found in the simulations strongly favor protostellar models with cool atmospheres and highly extended envelopes (Hosokawa et al 2013;Schleicher et al 2013;Woods et al 2017;Haemmerlé et al 2017), implying that feedback is rather inefficient. Under such conditions, final black hole masses of 10 5 M can be reached based on the results of cosmological simulations (Latif et al 2013b;Umeda et al 2016).…”
Section: Introductionmentioning
confidence: 89%
“…The large accretion rates of 0.1 M yr −1 or more found in the simulations strongly favor protostellar models with cool atmospheres and highly extended envelopes (Hosokawa et al 2013;Schleicher et al 2013;Woods et al 2017;Haemmerlé et al 2017), implying that feedback is rather inefficient. Under such conditions, final black hole masses of 10 5 M can be reached based on the results of cosmological simulations (Latif et al 2013b;Umeda et al 2016).…”
Section: Introductionmentioning
confidence: 89%
“…The limit in mass above which accreting SMSs become GR unstable has been investigated in numerical simulations (Umeda et al, 2016;Woods et al, 2017;Haemmerlé et al, 2018b), and are shown on Fig. 5.…”
Section: The Final Collapse Of Smssmentioning
confidence: 99%
“…Convective heat transport is included only when a zone is convective by the Ledoux criterion. For accreting models, accretion is carried out as described in Woosley et al (2004) and Woods et al (2017).…”
Section: Simulating Supermassive Stars With Keplermentioning
confidence: 99%
“…In the atomic-cooling halo scenario (e.g., Bromm & Loeb 2003;Dijkstra et al 2008; Regan et al 2017), photo-destruction of the molecular hydrogen in a primordial halo at z ∼ 10-20 by an intense Lyman-Werner flux permits the halo gas to reach ∼ 8 kK before radiative losses from atomic hydrogen line transitions can lock in the temperature, bringing the Jeans mass and typical infall rates up to ∼ 100 kM ⊙ and 0.1-10 M ⊙ yr −1 . The fates of the resulting objects have been examined in increasing detail in the last few years (e.g., Hosokawa et al 2013;Woods et al 2017;Haemmerlé et al 2018b). Large baryonic streaming velocities may be able to assist in suppressing star formation in the process, and may even be sufficient in the absence of a substantial Lyman-Werner flux (e.g., Tanaka et al 2013).…”
Section: Introductionmentioning
confidence: 99%